Investigating Cultures of Equality - Golańska, Dorota; Różalska, Aleksandra M.; Clisby, Suzanne (Taylor & Francis, 2022)
This volume explores the processes of investigating cultures of equality and sets out an epistemological framework for generating a more just and response-able knowledge. It offers a tapestry of inventive, self-reflexive, collective, and situated praxis of conducting politically informed research. Such efforts contest-or occasionally reinvent-the social and cultural worlds that we currently inhabit, in an attempt at building cultures of equality across different locations and contexts. The book engages with the idea of producing knowledge with others, indicating the political potential of scientific practice and offering a view of knowledge as a collective affective-intellectual effort. It provides an inventory of creative engagements with concepts and methodologies enabling production of socially responsible knowledges. By critically exploring new possibilities of scientific inquiry, the contributors reflect on how knowledge can be generated to serve the political agenda of movements for equality and social justice. The chapters also elucidate different conceptualisations of and approaches to who the researcher is and how they interact with cultural and social worlds.